Improving Students' English Speaking Ability Through Free Story Method with Picture Card Media - Marzuki Marzuki; Samnia Samnia; Ratna Ratna (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study addresses students' problems related to their low ability to speak English in class IX-A of SMPN 17 Kep. Masaloka Raya. This study uses the Free Story method with picture card media. The design of this research is classroom action research which is carried out for two cycles. The results showed that in the first cycle, there were 18 students (66.67%) whose speaking ability scores were equal to or above the KKM, and there were nine students (33.33%) whose scores were below the KKM. Because these results do not meet the success criteria that have been set, namely, at least 85% of students have a score equal to or above the KKM, the research continues in the next cycle by first revising some learning steps that are considered not too maximal. The research results in Cycle II showed that there were 26 students (96.30%) whose scores were equal to or above the KKM, and there was one student (3.70%) whose scores were still below the KKM. With the achievement of the success targets that have been set, it can be concluded that the use of the Free Story method with picture cards media succeeded in improving the speaking ability of Class IX A students at SMPN 17 Kp. Masaloka Raya.